The Effect of Variability of Practice on the Basketball Free-Throw Learning under Implicit and Explicit Conditions - Behrouz Abdoli; Alireza Farsi; Masoud Ariafar (University of Tehran, 2017)
Motor and field characteristic change is called variability of practice that the learner experiences during skill practice. This study was designed to compare the effect of variability of practice on the basketball free-throw learning in implicit and explicit conditions. For this purpose, 40 male (20-27 years old) Shahid Beheshti University students were voluntarily selected and were randomly divided into four groups: implicit learning with variable practice, implicit learning with constant practice, explicit learning with variable practice and explicit learning with constant practice after a pretest. Variable practice groups performed 45 throws from 1.5, 3 and 4 meters distances from the target while constant practice groups had these throws from 3 meters distance each session for 6 days. Implicit learning groups performed a secondary task of counting from 1000 in a reverse order for every triad number along with the free-throw task. But the explicit learning groups performed the free-throw task​ ​without a secondary task. The acquisition, retention (48 hours after the last acquisition phase) and transfer (from a 4.6 meters distance) tests were conducted. For data analysis, analysis of variance with repeated measures, two-way ANOVA and Tukey post hoc test were used (P<0.05). The results showed that all groups improved in the acquisition phase (P>0.001) while the main effect of learning and practice was not significant (P>0.05). In addition, in the retention and transfer phases, the main effect of learning type, practice type and the interaction between practice and learning was not significant (P>0.05). Therefore, the results of the present study disagreed with Schmidt's schema theory.